2010
DOI: 10.3233/jad-2010-1228
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Field Treatment Protects Against and Reverses Cognitive Impairment in Alzheimer's Disease Mice

Abstract: Despite numerous studies, there is no definitive evidence that high-frequency electromagnetic field (EMF) exposure is a risk to human health. To the contrary, this report presents the first evidence that long-term EMF exposure directly associated with cell phone use (918 MHz; 0.25 w/kg) provides cognitive benefits. Both cognitive-protective and cognitive-enhancing effects of EMF exposure were discovered for both normal mice and transgenic mice destined to develop Alzheimer's-like cognitive impairment. The cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
173
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 197 publications
(186 citation statements)
references
References 39 publications
(57 reference statements)
12
173
1
Order By: Relevance
“…Intriguingly, a positive effect of RF‐EMF was reported in an AD mouse model. Previous studies have demonstrated that long‐term RF‐EMF exposure may have beneficial effects on cognitive deficits of AD transgenic mice [Arendash et al, 2010; Jeong et al, 2015], and this effect might be related to reduced Aβ deposition. Therefore, we used the 5xFAD transgenic mouse model, which shows AD‐like pathology, such as early Aβ plaque formation in brain parenchyma and behavioral deficits [Oakley et al, 2006].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Intriguingly, a positive effect of RF‐EMF was reported in an AD mouse model. Previous studies have demonstrated that long‐term RF‐EMF exposure may have beneficial effects on cognitive deficits of AD transgenic mice [Arendash et al, 2010; Jeong et al, 2015], and this effect might be related to reduced Aβ deposition. Therefore, we used the 5xFAD transgenic mouse model, which shows AD‐like pathology, such as early Aβ plaque formation in brain parenchyma and behavioral deficits [Oakley et al, 2006].…”
Section: Discussionmentioning
confidence: 99%
“…We observed no effects of RF‐EMF on behavioral function and APP processing, including Aβ deposition, in 5xFAD mice. However, long‐term RF‐EMF exposure (918 MHz for 8 months) protected against cognitive impairment, which was demonstrated by radial arm water maze and cognitive interference task reported in transgenic APPsw mice [Arendash et al, 2010]. In addition, 8 months exposure to 1950 MHz RF‐EMF has been reported to significantly improve Y‐maze and passive avoidance performance in 5xFAD mice [Jeong et al, 2015].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations